2021
DOI: 10.4274/gulhane.galenos.2020.1312
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of parents concerning childhood vaccine refusal and factors affecting vaccination in Konya

Abstract: The purpose of this study was to reveal the opinions, knowledge, and attitudes of parents in Konya, who refuse vaccination, concerning vaccine refusal. Methods:The study has a cross-sectional design. The research data were collected in 2019 using a survey form developed by the researchers. The survey form was filled out by the parents of children in the 0-4 age group who had not been vaccinated in Konya and its districts in 2017. We were able to reach 801 out of 923 children who had not been vaccinated and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…According to a literature survey, the rate of those who consider foreign production of vaccines as a problem was determined 18% and 9% by Hough-Telford et al (27) and Massimi et al (28), respectively. Furthermore, İlter conducted a study with families who refuse vaccinations and he found that about 70% of families believe that vaccines are recommended to protect the commercial interests of pharma companies (29). To strengthen the public confidence in vaccines and reduce vaccine refusal rates, starting domestic production of vaccines could be very effective.…”
Section: Discussionmentioning
confidence: 99%
“…According to a literature survey, the rate of those who consider foreign production of vaccines as a problem was determined 18% and 9% by Hough-Telford et al (27) and Massimi et al (28), respectively. Furthermore, İlter conducted a study with families who refuse vaccinations and he found that about 70% of families believe that vaccines are recommended to protect the commercial interests of pharma companies (29). To strengthen the public confidence in vaccines and reduce vaccine refusal rates, starting domestic production of vaccines could be very effective.…”
Section: Discussionmentioning
confidence: 99%
“…Mães de crianças menores de cinco anos de idade 23 participantes E18 (37) Revelar as opiniões, conhecimentos e atitudes dos pais que recusam a vacinação infantil.…”
Section: Idunclassified
“…Mothers of children under five years of age 23 participants S18 (37) Reveal the opinions, knowledge and attitudes of parents who refuse childhood vaccination.…”
Section: Mothers Of Children Under Fivementioning
confidence: 99%